The use of metagenomic sequencing as a tool for pathogen discovery with further investigation of novel reptilian serpentoviruses - Hoon-Hanks, Laura L., author; Stenglein, Mark, advisor; Ebel, Gregory, committee member; Sloan, Daniel, committee member; Han, Sushan, committee member (Colorado State University. Libraries, 2019)
To view the abstract, please see the full text of the document.
Keywords: nidovirus; serpentovirus; metagenomic; snake; sequencing